African trade policy in the 1990s: Political economy or technocratic reforms? - Chris Jones; Oliver Morrissey; Doug Nelson (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2008)
The majority of African countries implemented import liberalisation in the 1990s. This paper explores factors that may explain the pattern of protection and of tariff reform. We consider political economy explanations, motivated specifically by the Grossman and Helpman (1994) model of protection in response to industry lobbies, and the possibility that reforms are technocratic. Using industry-level data for a sample of six African countries, we find limited evidence that political economy factors have influenced the pattern of tariffs or tariff reductions since the early 1990s. One result does appear frequently: relative sector size (measured by the number of employees or establishments) appears to be associated with the relative level of protection. We then explore various descriptive statistics for tariff changes in seven African countries. The analysis suggests that the pattern of tariff reductions was essentially technocratic in structure - across the board reduction in average tariffs and in the dispersion of rates, with larger proportional reductions for higher tariffs - consistent with policy reforms being guided by the World Bank. While political economy factors may have influenced the initial pattern of protection, the technocratic reforms since the early 1990s have diluted political economy influences on average and relative protection.
Keywords: F13; O20; O55; 330; Pattern of Protection; Tariff Reform; Political Economy; Africa; Außenhandelspolitik; Protektionismus; Außenhandelsliberalisierung; Zolltarif; Wirtschaftsreform; Wirtschaftspolitik; Afrika